Alasan Pemerintah Etiopia Membangun Grand Ethiopian Renaissance Dam (GERD) di Kawasan Sumber Daya Air Lintas Batas Negara - Mohdar, Muhammad; Dharmiasih, D.A. Wiwik; Prameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   This research aims to describe the reason of the Government of Ethiopia on developing Grand Ethiopian Renaissance Dam (GERD) by using a qualitative method. The development of a controversial GERD, in fact, triggers a few protests from several parties like Egypt who may be damaged by it. Referring to the past historical agreements, Egypt even threatens if Ethiopia takes any action which disrupts the flow of Nile coming to that most downstream country in the Horn of Africa. However, Ethiopia, a smaller country comparing to Egypt intensively look forward upon completion of GERD despite the potential conflict. Therefore, Researcher uses two main concepts, which are water security and national interest in order to answer the motive behind Ethiopia’s brave action. This research perceives that Ethiopia is having sort of National Interest to achieve the water security within the country through the development of huge and multi-functioned dam like GERD.   Keyword: Ethiopia, Water Security, National Interest, Grand Ethiopian Renaissance Dam